2009
DOI: 10.1007/s11423-009-9128-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of class lecture webcasting on attendance and learning

Abstract: The present study investigated the impact of class lecture webcasts on students' attendance and learning. The research design employed four data collection methods in two class sections-one with webcast access and another without-of the same course taught by the same instructors. Results indicated the following four major findings. (1) The availability of webcasts negatively impacted student attendance but the availability of other online resources such as PowerPoint slides had a greater negative impact on att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
260
4
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(316 citation statements)
references
References 20 publications
22
260
4
13
Order By: Relevance
“…The results were in general agreement with the results of research carried out elsewhere, e.g. [1], [2], [11], [12].…”
Section: A Suitability For the Purposesupporting
confidence: 91%
“…The results were in general agreement with the results of research carried out elsewhere, e.g. [1], [2], [11], [12].…”
Section: A Suitability For the Purposesupporting
confidence: 91%
“…O'Bannon et al (2011) found no differences in achievement when comparing students who had experienced lecture podcasts to students who had attended parallel lectures. In a study by Traphagan et al (2010), students who had access to lecture podcasts as well as to face-to-face lectures did not differ in achievement from students who only had access to the face-to-face lectures.…”
Section: Learning and Achievement In Face-to-face Lectures And With Lmentioning
confidence: 89%
“…In a study by Homer et al (2008) students felt motivated and invigorated by the lecturer shown in the podcasts. In other studies, students reported being less anxious when they could take notes from lectures they viewed later on their own without having to worry about missing important information (Owston et al 2011), or that viewing lecture podcasts helped them to reduce their anxiety before a test situation (Pilarski et al 2008;Traphagan et al 2010). …”
Section: Satisfaction and Emotions In Face-to-face Lectures And With mentioning
confidence: 96%
See 1 more Smart Citation
“…Researchers tried to improve the quality of the recordings by addding more advanced interaction options [3,4], automated capturing [6,1,27] and camera control [13], search options [11] and mobile solutions [16]. More recently there also has been more focus on the use of the recorded lectures by students [23,9,21], their use in university settings [28,17], its use for students with a handicap [18] and possible impact of recorded lectures on the attendance of students [26,22]. Little is known, still, about the way P r e p r i n t in which students navigate within the recordings or how they find (the parts of) the recordings they want to watch.…”
Section: Fig 1 Example Of a Recorded Lecturementioning
confidence: 99%